Task force’s work management of decreasing maternal and infant mortality numbers ant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal and infant mortality numbers maternal an - Eko Supeno, Evi Nur Handayani, (Opción, 2019)
This research aims to give an accurate and detailed picture of work management of a task force assigned to decrease maternal and infant mortality via comparative qualitative research methods. The result of this study shows that the task force performance can be seen from the scope of input, which is by the type of the task force, the development of the task force and the characteristics. In conclusion, the Satgas Penakib has been able to carry out its team duties and functions by using a gender approach to understand the requirement needed by all pregnant women in Surabaya